Secondary electron emission and yield spectra of metals from Monte Carlo simulations and experiments. (19th December 2018) - Azzolini, Martina; Angelucci, Marco; Cimino, Roberto; Larciprete, Rosanna; Pugno, Nicola M; Taioli, Simone; Dapor, Maurizio
Abstract: In this work, we present a computational method, based on the Monte Carlo statistical approach, for calculating electron energy emission and yield spectra of metals, such as copper, silver and gold. The calculation of these observables proceeds via the Mott theory with a Dirac–Hartree–Fock spherical potential to deal with the elastic scattering processes, and by using the Ritchie dielectric approach to model the electron inelastic scattering events. In the latter case, the dielectric function, which represents the starting point for the evaluation of the energy loss, is obtained from experimental reflection electron energy loss spectra. The generation of secondary electrons upon ionization of the samples is also implemented in the calculation. A remarkable agreement is obtained between both theoretical and experimental electron emission spectra and yield curves.